South Asian Mammals : An updated Checklist and Their Scientific Names - Srinivasulu, Chelmala; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This book is an up-to-date comprehensive resource on the names (scientific, English and vernacular) of the mammals of South Asia.This work is first of its kind that deals with explanation of names of mammals at the species and subspecies level.
Contents -- Preface............................................................ix -- Acknowledgements ..................................................xi -- About the Book ................................................... xiii -- Author ...........................................................xv -- List of Abbreviations and Symbols ....................................xvii -- Chapter 1 --South Asian Mammals: An Updated Checklist ..................1 -- Checklist of Mammals of South Asia .........................1 -- Chapter 2 --Understanding Scientific Names ............................ 33--Parts of Scientific Names .................................. 33 -- Codes of Nomenclature ...................................34 -- Principle of Binomial Nomenclature .......................36 -- Principle of Typification ................................ 37 -- Principle of Priority ....................................37 -- Principle of Homonymy ................................38 -- Criteria of Availability ....................................38 -- Synonyms ..............................................38 -- Types ................................................. 39 -- Formation of Zoological Names ............................40 -- Analysis of Names ....................................... 41 -- Chapter 3 --Generic and Specific Names Explained .......................49 -- Chapter 4 --Dictionary of South Asian Mammalian Names ................225 -- Appendix I: List of Languages Used in Autochthonous and -- Vernacular Names --................................................289 -- Bibliography --.....................................................295 -- Index --........................................................... 323
Includes bibliographical references and index.
Also available in print format.
Keywords: Mammals -- South Asia; Mammals -- South Asia -- Nomenclature; NATURE / Animals / General; SCIENCE / Life Sciences / Evolution; Arrangement of Names; Artiodactylya; Codes of Nomenclature; Erinaceopmorpha; Proboscidea; Rodentia; Electronic books